The influence of fandom culture, social media and viral marketing on the popularity of the Film Mencuri Raden Saleh which causes Fear Of Missing Out (FOMO) symptoms in Indonesian society - Iqlima Az-Zahra Ciersya; Nur Afifah; Bintoro Bagus Purmono; Ramadania Ramadania; Karsim Karsim (International Journal of Applied Finance and Business Studies, 2023)
This research aims to investigate the influence of three main factors, namely Fandom Culture, Social Media, and Viral Marketing, on the popularity of the film "Mencuri Raden Saleh" and its impact on the emergence of Fear of Missing Out (FOMO) symptoms among the public. This film has received great enthusiasm from the audience and has become a highly anticipated work of cinema. This research method uses a questionnaire-based survey distributed to film viewers and fans by taking samples using a purposive sampling technique. Respondents consisted of 200 people who had watched the film "Mencuri Raden Saleh" in Indonesia. Data was analysed using Structural Equation Modeling (SEM) and AMOS software. The findings show that all the independent variables have a positive influence on FOMO. However, the proposed mediating variable, namely Movie Popularity, does not have a significant impact on the relationship between the independent and dependent variables. This research implies that marketers and filmmakers can consider using these variables as strategies to increase the level of audience engagement and enthusiasm for films. Apart from that, it is also necessary to consider other factors that might influence the symptoms of FOMO in the film context